2022
DOI: 10.1111/cbdd.14111
|View full text |Cite
|
Sign up to set email alerts
|

Novel hybrid virtual screening protocol based on pharmacophore and molecular docking for discovery of GSK‐3β inhibitors

Abstract: GSK‐3β is a member of the GSKs subfamily and plays a major role in the regulation of transcriptional elongation, which has attracted widespread attention as a therapeutic target for AD. In this study, by combining pharmacophore‐based virtual screening and kinase inhibition assays, we have successfully identified four small molecules that inhibit GSK‐3β activity at micromolar potency. These hit compounds showed drug‐like properties according to Lipinski's rule of five and ADMET. An inter‐complex interaction stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This study evaluated the drug-like properties of AIL using the SwissADME database by applying Lipinski’s rule, a guideline for drug design and screening ( Liu et al, 2023 ). The results revealed that the ADME parameters of AIL (MW = 376.40 Da; Hdon = 3; Hacc = 7; AlogP = −0.32; RBN = 0) meet Lipinski’s rule parameters, suggesting satisfactory medicinal properties.…”
Section: Discussionmentioning
confidence: 99%
“…This study evaluated the drug-like properties of AIL using the SwissADME database by applying Lipinski’s rule, a guideline for drug design and screening ( Liu et al, 2023 ). The results revealed that the ADME parameters of AIL (MW = 376.40 Da; Hdon = 3; Hacc = 7; AlogP = −0.32; RBN = 0) meet Lipinski’s rule parameters, suggesting satisfactory medicinal properties.…”
Section: Discussionmentioning
confidence: 99%